PHYTOCHEMICAL SCREENING STUDIES OF BIOACTIVE COMPOUNDS OF TAGETES ERECTA. - R. DEVIKA; JUSTIN KOILPILLAI (International Journal of Pharma and Bio Sciences, 2012)
African marigold (Tagetes erecta) has been used for medicinal purposes since prehispanic times. The various parts of the plant such as stem, leaf, flower and root were subjected to analysis the qualitative phytochemical constituents with two different solvents (ethyl alcohol and petroleum ether). About sixteen phytochemicals analysis were carried out, out of which six phytochemicals were identified in both the solvents predominantly.